2017
DOI: 10.6065/apem.2017.22.1.55
|View full text |Cite
|
Sign up to set email alerts
|

Growth without growth hormone in combined pituitary hormone deficiency caused by pituitary stalk interruption syndrome

Abstract: Growth hormone (GH) is an essential element for normal growth. However, reports of normal growth without GH have been made in patients who have undergone brain surgery for craniopharyngioma. Normal growth without GH can be explained by hyperinsulinemia, hyperprolactinemia, elevated leptin levels, and GH variants; however, its exact mechanism has not been elucidated yet. We diagnosed a female patient aged 13 with combined pituitary hormone deficiency (CPHD) caused by pituitary stalk interruption syndrome (PSIS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 13 publications
(17 reference statements)
0
13
0
Order By: Relevance
“…Therefore, PSIS should be included in the differential diagnosis of retarded growth and delayed puberty in children[ 48 ]. However, Lee et al [ 49 ] reported a case of PSIS with multiple hormone deficiencies that did not affect growth, and the specific mechanism is still unclear. Some other atypical initial manifestations also need to be kept in mind.…”
Section: Clinical Characteristicsmentioning
confidence: 99%
“…Therefore, PSIS should be included in the differential diagnosis of retarded growth and delayed puberty in children[ 48 ]. However, Lee et al [ 49 ] reported a case of PSIS with multiple hormone deficiencies that did not affect growth, and the specific mechanism is still unclear. Some other atypical initial manifestations also need to be kept in mind.…”
Section: Clinical Characteristicsmentioning
confidence: 99%
“…Also, the role of hypothyroidism, hypoadrenocorticism, and hypogonadism in NAFLD could not be ruled out.In childhood, the most common manifestation of PSIS is growth retardation due to GHD. However, there have been reports of growth occurring without GH ( 10 12 ). This phenomenon was initially observed in patients with hypopituitarism after craniopharyngioma surgery, and the underlying mechanism remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The phenomenon of normal growth in patients with confirmed growth hormone deficiency has been observed, although it is not fully understood. They seems to be similar to the case of a 16-year-old girl with PSIS and CPHD described by Lee et al ., who despite significant GH deficiency in the insulin test achieved the correct final height – 168 cm [ 26 ]. It is inquiring why in a patient with confirmed severe GHD periods with the inhibition of height velocity followed by a normal growth rate are observed, as in presented subjects No.1 and 11.…”
Section: Discussionmentioning
confidence: 99%